Experimental coevolution: rapid local adaptation by parasites depends on host mating system - Morran, Levi T. (2014)
Host-parasite interactions can drive rapid, reciprocal genetic changes (coevolution), provided both hosts and parasites have high heritabilities for resistance/infectivity. Similarly, the host’s mating system should also affect the rate of coevolutionary change in host-parasite interactions. Using experimental coevolution, we determined the effect of obligate outcrossing verses partial self-fertilization (mixed mating) on the rate of evolutionary change in a nematode host (Caenorhabditis elegans) and its bacterial parasite (Serratia marcescens). Bacterial populations were derived from a common ancestor. We measured the effects of host mating system on host adaptation to the parasite. We then determined the extent of parasite adaptation to their local host populations. Obligately outcrossing hosts exhibited more rapid adaptation to parasites than did mixed mating hosts. In addition, most of the parasites became adapted to infecting their “local” hosts; but parasites from obligately outcrossing hosts showed a greater level of local adaptation. These results suggest that host populations evolved along separate trajectories, and that outcrossing host populations diverged further than partially selfing populations. Finally, parasites “tracking” outcrossing host populations diverged further than parasites tracking the partially selfing host populations. These results show that the evolutionary trajectories of both hosts and parasites can be shaped by the host’s mating system.